Unilateral blindness associated with steroid‐responsive meningitis arteritis in a 9‐month‐old Beagle. Issue 1 (21st December 2021) - Tang, Charis; Álvarez, Patricia; Manning, Susan; Wessmann, Annette
Abstract: A 9‐month‐old Beagle presented with a 24‐hour history of lethargy, pyrexia, and cervical and thoracolumbar pain. Cranial nerve examination revealed an absent menace response, an absent dazzle reflex, and absent direct and left‐to‐right consensual pupillary light reflexes in the left eye, indicating a non‐visual eye. Funduscopic examination and electroretinography were unremarkable. Complete blood profile showed moderate neutrophilia, monocytosis and elevated C‐reactive protein. Cerebrospinal fluid analysis revealed a neutrophilic pleocytosis. Magnetic resonance imaging of the head, thoracic and abdominal imaging, urinalysis, joint taps and infectious disease titres were unremarkable. A diagnosis of steroid‐responsive meningitis arteritis (SRMA) with left optic nerve involvement was concluded. Blindness has not been reported in cases with SRMA. An extension of the leptomeningeal inflammation into the optic nerve sheaths is hypothesized as the underlying pathophysiology. SRMA should be considered as a cause of blindness in the presence of other clinical signs compatible with this condition.